Fungsi Kewang Dalam Mencegah Abrasi Pantai Dan Kerusakan Lingkungan Wilayah Pesisir Negeri Adat - Noya, Ekberth Vallen (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2025)
The kewang institution not only functions as a guardian of ecological balance but also as a protector of the customary land rights of indigenous communities concerning natural resource management. In Central Maluku, kewang plays a crucial role in regulating access, utilization, and conservation of marine life and forests, involving the mechanism of sasi or prohibitions that must be adhered to by the local community. With deep roots in local cultural values, kewang has a clear organizational structure and the authority to enforce customary laws, including prohibitions and sanctions for violators. Kewang plays a key role in maintaining a harmonious relationship between humans and nature while encouraging the community to take responsibility for the sustainable use of natural resources. Through this role, indigenous communities in Central Maluku strive to preserve traditions and local knowledge that have existed for generations. Therefore, understanding and preserving the kewang institution is vital in efforts to maintain cultural identity and environmental sustainability in the region.